Teaching Styles of Teachers as an Effort to Realize Effective Classroom Management in Senior Classes at MIN 1 Lombok Barat - Lalu Maksudy Mulkan; Lalu Mathlubi Ali Zunnun (Jurnal Ilmiah Profesi Pendidikan, 2026)
This study aims to examine the relationship between teachers’ teaching styles and the effectiveness of classroom management in upper-grade classes at MIN 1 Lombok Barat. The problem addressed in this research is the frequent ineffectiveness of classroom management, which is suspected to be influenced by the variations in teaching styles used by teachers. This research employed a quantitative approach with a correlational design. The population consisted of all upper-grade teachers at MIN 1 Lombok Barat, with a sample of 6 teachers selected using purposive sampling. Data were collected through a structured questionnaire adapted from validated teaching style and classroom management scales. Descriptive statistics and Pearson product-moment correlation analysis were used to analyze the data. The results indicate that most teachers tend to apply a classical teaching style, with limited use of personalized or technology-integrated approaches. The statistical analysis showed a significant positive correlation between teaching styles and classroom management effectiveness (r = 0.712, p < 0.05), suggesting that more adaptive and student-centered teaching styles contribute to better classroom control, student engagement, and learning outcomes. The study concludes that teaching styles play a critical role in shaping effective classroom management, particularly in upper elementary education contexts. This research contributes both theoretically and practically: theoretically by reinforcing the linkage between pedagogical methods and classroom dynamics, and practically by offering insights for teacher training programs and school policy development focused on instructional improvement. Further research is recommended to explore these relationships using larger sample sizes and across diverse school contexts to generalize the findings more broadly.